Selective induction of p53 and chemosensitivity in RB-deficient cells by E1A mutants unable to bind the RB-related proteins - Samuelson, Andrew V. (The National Academy of Sciences of the USA, 1997)
The adenovirus E1A oncoprotein renders primary cells sensitive to the induction of apoptosis by diverse stimuli, including many anticancer agents. E1A-expressing cells accumulate p53 protein, and p53 potentiates drug-induced apoptosis. To determine how E1A promotes chemosensitivity, a series of E1A mutants were introduced into primary human and mouse fibroblasts using high-titer recombinant retroviruses, allowing analysis of E1A in genetically normal cells outside the context of adenovirus infection. Mutations that disrupted apoptosis and chemosensitivity separated into two complementation groups, which correlated precisely with the ability of E1A to associate with either the p300/CBP or retinoblastoma protein families. Furthermore, E1A mutants incapable of binding RB, p107, and p130 conferred chemosensitivity to fibroblasts derived from RB-deficient mice, but not fibroblasts from mice lacking p107 or p130. Hence, inactivation of RB, but not p107 or p130, is required for chemosensitivity induced by E1A. Finally, the same E1A functions that promote drug-induced apoptosis also induce p53. Together, these data demonstrate that p53 accumulation and chemosensitivity are linked to E1A’s oncogenic potential, and identify a strategy to selectively induce apoptosis in RB-deficient tumor cells.